Standard enteral feeding improves nutritional status compared with hospital-prepared blended formula among Intensive Care Unit (ICU) patients - Mousavi Jazayeri, Seyed Mohammad Hosein; Ostadrahimi, Alireza; Safaiyan, Abdolrasoul; Hashemzadeh, Shahryar; Salehpour, Firouz (Progress in Nutrition, 2016)
Introduction: There have been great advances in enteral nutrition among critically ill patients in recent decades. However, manufactured standard enteral formula is a new material in Iran and most hospitals are still opting to use traditional hospital-prepared blended formulas. Objective: To evaluate effects of standard enteral feeding for improving nutritional status compared with hospital-prepared blended formula among Intensive Care Unit (ICU) patients. Methods: Forty patients participated in enteral feeding by the standard system and forty patients participated in enteral feeding by hospital-prepared blended formulas. Results: Albumin was much increased in the standard enteral feeding group compared to hospital-prepared blended formulas (P<0.005). There were significant differences in results of albumin, hemoglobin (Hg) and calcium before and after feeding. Conclusion: The macronutrients intake was elevated after standard enteral nutrition and helped patients to recover. The standard enteral formula has more benefits than hospital-prepared blended formulas for ICU patients and medical care givers should be advised and taught to use it rather than hospital-prepared blended formula.